Analysis and Implementation of 3D Magnetic Field Shaping via a 2D Planar Transmitting Coil Array - Kang, Ning; Shao, Yaoxia; Liu, Ming; Ma, Chengbin (IEEE transactions on power electronics, 2022)
Wireless power transfer (WPT) systems operating at several MHz are known to be advantageous for realizing high spatial freedom of power transfer and compact and lightweight designs. The combined use of multiple transmitting (Tx) coils for magnetic field shaping is expected to further increase the spatial freedom. This article studies an extendable planar Tx-coil array architecture. This architecture provides new conveniences for the MHz WPT systems to efficiently charge devices in 3D space. Time-domain and phasor-domain modelings are carried out in turn to analyze the magnetic field shaping effect under the current phase shift modulation of the Tx coils. An overlap design of the Tx-coil layout is also developed to minimize the cross coupling between the coils, which reduces the interference between Tx coils. Finally, the above concepts are experimentally implemented. The results clearly demonstrate the new advantages of the planar Tx-coil array-based magnetic field shaping, in terms of spatial freedom of the power transfer, efficiency, and output power capability, when charging receivers with six-degrees-of-freedom positions and orientations in 3D space. For instance, a perpendicular receiver in the center of the Tx-coil array can be charged with 82% dc-dc efficiency and 45 W, which is difficult for a conventional single Tx-coil solution.